Technological change and innovation in Latin American emerging economies: The pork industry of Antioquia, Colombia (2014)
Innovation and technology, in appropriate business environments, are considered improvement and survival tools directly related to the establishment of competitive advantages. However, this must be accompanied by a growing economy, and, in some cases, governmental policies that encourage the industry. This chapter inquires about several factors involved in the innovation and technological change of the pork industry in Antioquia, Colombia, based on original research results and other contributions of the authors. The managerial assumption is simple: free trade and strategic moves of the biggest competitors indicate that Small- and Medium-Sized Enterprises (SMEs) in the pork industry must accelerate their technological change via innovation management by addressing different factors that are hindering the establishment of competitive advantages. The authors offer a possible path of action from a management perspective to support that the industry will form an oligopoly should innovation management not occur. © 2014 by IGI Global. All rights reserved.